Big data, bigger opportunities - Badrick, Tony (Journal of Laboratory and Precision Medicine, 2017)
It is likely that somewhere between 70–80% of the information in the electronic health record is pathology data (1). These data are relatively readily available and represent the collective experience of the pathology profession. The amount of this data is enormous. There are more than 500 million pathology tests performed each year in Australia alone (2).